Transaction Fraud Detection in Savings and Loan Cooperatives Using Xgboost with Shap Explanations (Shapley Additive Explanations) - Indra Marto Silaban; Muhammad Syahputra Novelan; Muhammad Irfan Sarif (Cattleya Darmaya Fortuna, 2026)
Savings and loan cooperatives play a crucial role in supporting the community's economy. With the motto